The Interpretation of Organizational Culture and Internal Control in Preventing Fraud: A Case Study in the Bengkulu Provincial Government - Pesi Suryani; Lasando Lumban Gaol; Eko Kuswanti; Sri Sukatmi (UNIB Press, 2025)
This study explores the factors contributing to fraud in the public sector through the lens of the Pentagon Theory and examines how organizational culture and internal control play a role in preventing fraud in government institutions. A qualitative approach with a case study method was employed, focusing on government agencies within the Bengkulu Provincial Government. Data were collected through in-depth interviews with employees and document analysis related to internal control systems. The findings reveal that weak organizational culture and ineffective implementation of internal controls are the primary factors that create opportunities for fraud. Additionally, pressure and rationalization within the bureaucratic environment further drive individuals to commit fraudulent acts. Moreover, the low expectation of punishment for fraud perpetrators exacerbates the situation and weakens existing prevention mechanisms. These findings reinforce the Pentagon Theory by highlighting the significant role of organizational culture in fraud prevention. Therefore, government institutions must strengthen integrity-based organizational culture and enhance the effectiveness of internal controls to mitigate fraud risks. This study emphasizes the interpretation of organizational culture within the context of the Pentagon Theory and underscores the critical role of internal control in fraud prevention in the public sector, particularly in local government environments.